Pengaruh Kemampuan Kognitif terhadap Hasil Pembelajaran Bola Basket - Mirza Awali (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The method used in this research is the experimental method with two group pretest postest designs. The population of this research are 20 male students of 11 grade in SMA Negeri 2 Lahat. There are 20 students as the sample which are divided to 10 students in high cognitive group and the other 10 students in low cognitive group. This research takes 1 months, including 12 times meeting for exercise, with the frequency three times a week. The instrument that is choosen by the writer is intellegence test IQ for senior high school students to determine the intellegency level and for the basketball skill first and last test of basketball skill, there are three test with the r validity level is 0,89 that are throwing and catching ball, shooting ball into the basket, and dribbling ball test. Keywords: Cognitive Ability, The Result of Basketball Learning